Effectiveness of Yoga in Reducing Menstrual Pain Intensity Among Adolesents: a Comparative Study Before and After Intervention - Gusti Ayu Eka Utarini; Ni Luh Putu Sinta Dewi; Ni Luh Putu Sri Erawati; Listina Ade Widya Ningtyas (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2025)
Menstrual pain occurs in more than 90%Â of adolescence through out the world who experience pain during menstruation and 10% experience severe menstrual pain. Treatment of menstrual pain can be done using pharmacological or non-pharmacological methods. One non-pharmacological treatment is yoga therapy. The aim of this study was to determine the difference in the intensity of menstrual pain before and after yoga therapy was given to adolescent at SMAN 2 Bangli. The design of this research is quasi-experimental with a one group pre test-posttest design. The sampling technique used Non Probability Sampling, Purposive Sampling with a total of 30 respondents. The instrument used was the Numeric Rating Scale measurement sheet. The results of data analysis show that there is a difference before and after being given yoga therapy with a value of p = 0.000 (Î± < 0.05). The level of menstrual pain inÂ adolescents obtained the lowest pretest score was two and the highest scorewas six and the median value was four. In the post test results showed that the lowest score was one, the highest was five and the median was two. This demonstrates a significant difference in menstrual pain intensity among adolescentÂ before and after yoga therapy.